PENAMBAHAN FERMENTASI DAUN LAMTORO (Leucaena leucocephala) PADA PAKAN UNTUK PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN LELE SANGKURIANG (Clarias gariepinus) - Yasna Hoerunnisa; Mad Rudi; Ahmad Beni Rouf (Universitas Muhammadiyah Gresik, 2024)
Lamtoro leaves (Leucaena leucocephala) are used as feed ingredients because they contain a lot of protein but are hampered by the high fiber content but can be reduced by fermentation to cover the smell of lamtoro leaves which fish do not like. This research aims to examine the effect of fermenting lamtoro leaves into artificial feed for sangkuriang catfish (C.gariepinus) on the growth and survival of sangkuriang catfish (Clarias gariepinus). This research used 120 Sangkuriang catfish with ± 3 grams and a length of ± 5-6 cm. This research method uses a quantitative and experimental approach using a Completely Randomized Design (CRD) consisting of four and three replications consisting of control, 10% lamtoro leaf fermentation, 15% lamtoro leaf fermentation, and 20% lamtoro leaf fermentation. The research observation parameters were absolute weight, absolute length, feed conversion, specific growth rate, and survival of sangkuriang catfish (Clarias gariepinus). The results showed that treatment with the addition of fermented lamtoro leaves had no significant effect (P>0.05) on the survival and growth of sangkuriang catfish. The conclusion from this research is that fermentation of lamtoro leaves has no significant effect on the growth and survival of sangkuriang catfish (Clarias gariepinus).